O ativismo judicial em face da judicialização de questões ligadas à saúde: uma ofensa ao princípio da separação dos poderes - Ehrlich, Emerson Luis (2018)
The effectiveness of the right to health in Brazil has been the subject of controversial debates, involving questions about the implementation of public policies by the Executive Power and their effectiveness, in front of the increasing need of the emergency care population at the Public Health System. Queues of people in public hospitals waiting for service, patients waiting in hallways, waiting for medical specialists for surgery for the placement of prostheses and specialized treatments could justify, in theory, the filing of lawsuits seeking injunctions issued and require the executive power to comply with its burden only for certain people, who sought the support of the Judiciary. The failure in complying public goals established by law, as well as the neglect experienced by the public health in Brazil, today, the basis for judicial activism, which is effective at any given time, but on the other hand, disrupted government programs in its financial planning, since it withdrew public funds from certain projects and forced them to place them in the individual care of certain patients who used access to the Judiciary to meet the urgency that the individual case required. The judicial activism, similar as is done today in the country, invading powers of other powers, since the competence to legislate is not the judiciary, as well as the responsibility of the Executive power the management of public funds, not fitting the other powers interfering with duties provided for in the Federal Constitution of 1988.